Participação social e estratégia saúde da família : desvelando fragilidades e possibilidades - Furlanetto, Camila Fressatti (Universidade Federal de São Carlos, 2014)
The participation and the social control are guiding principles of SUS and for democratization of the system. The health acting and services management should express joint definitions between the government and population. The 8.142/1990 Law establishes as instances for participation and social control in the Health the counsels and the conferences. The Family Health Strategy (FHS) could be considered an easier locus of the materialization of the social participation because of the link possibility with the user population. Considering this hypothesis, the research sought to analyze the users and Health worker’s perceptions of the Family for the social participation, seeking for the social effective control in health. It was held with workers and users of two Family Health Units in the São Carlos county, from the qualitative analysis, up with the application of semi structured interviews and thematic analysis, whose origins three categories(i) challenges for the effectiveness of the social participation in the FHS; (ii) participation spaces or just completion of formalities?; (iii) FHS: potentiality for social participation. The results of this study allowed unveiling various fragilities that figures as challenges for the social participation in the researching field, such as: lack of information/comprehension, exposition and power relations and welfares/accommodation. The institutionalized spaces for the participation and social control addressed in this study were the Municipal Health Conferences and the locals Management Councils, the effectiveness of them were analyzed negatively due lack of support and government participation. The research allowed unveiling also potentials as the counsels’ effort and the capacity spaces done between the team and the users members of the Management Councils in the Family Heath Units. Lastly, the participants perception strengthens the challenge that is the social participation in the SUS. As contribution, the needing pointing of more investment and attention to this spaces from the recognition of their potentialities.
Keywords: Controle social; Estratégia saúde da família; Participação social; Sistema único de saúde; Social control; Family health; Social participation; CIENCIAS DA SAUDE